A new quantitative X‐ray system for micro‐PIXE analysis. (16th May 2017) - Pallon, Jan; De La Rosa, Nathaly; Elfman, Mikael; Kristiansson, Per; Nilsson, E.J. Charlotta; Ros, Linus
Abstract : Particle Induced X‐ray Emission is a well‐established technique for quantitative elemental analysis down to trace levels. During microbeam analysis, where the beam is collimated and focused into a small spot, the beam current reduces to nA or less. The generation of characteristic X‐rays is reduced in the same proportion, leading to long data‐acquisition times. This can partly be compensated for by using detectors with a large solid angle. In this work, the performance of an annular eight‐element silicon drift detector with a total solid angle of 261 msr is described. The initial calibration of the detector was performed using thin elemental standards. Charge measurement was carried out both in a Faraday Cup positioned after the sample and by a pre‐sample electrostatic deflection system sampling the beam charge into another Faraday Cup. The two methods were used in parallel and compared during the calibration measurements. A recently installed Versa Module Europe (VME) based data acquisition system equipped with, for example, multi‐hit time‐to‐digital converters, amplifiers, and 32‐channel scalers, was used to record data in event‐by‐event mode for simultaneous data evaluation on multiple computers. Off‐line dead time and pile‐up corrections were made on the event data that was sorted into spectra and fitted with the GeoPIXE software. The pre‐sample deflection charge measurement gave consistent values for the calibration, and this is an important observation implying that non‐conductive and thick samples will be able to quantify without the use of internal standards. Copyright © 2017 John Wiley & Sons, Ltd.